2015
DOI: 10.1007/s00277-015-2393-0
|View full text |Cite
|
Sign up to set email alerts
|

All-trans retinoic acid with daunorubicin or idarubicin for risk-adapted treatment of acute promyelocytic leukaemia: a matched-pair analysis of the PETHEMA LPA-2005 and IC-APL studies

Abstract: Front-line treatment of acute promyelocytic leukaemia (APL) consists of all-trans retinoic acid (ATRA) and anthracycline-based chemotherapy. In this setting, a comparison of idarubicin and daunorubicin has never been carried out. Two similar clinical trials using ATRA and chemotherapy for newly diagnosed APL were compared using matched-pair analysis. One was conducted by the PETHEMA/HOVON group with idarubicin and the other by the International Consortium on APL (IC-APL) using daunorubicin. Three hundred and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 19 publications
1
24
0
8
Order By: Relevance
“…No studies have directly compared the type of anthracycline used for induction and consolidation, although a recent matched‐pair analysis comparing idarubicin and daurorubicin showed no significant difference in antileukaemic effect (Sanz et al , ).…”
Section: Open Issues With Atra and Chemotherapymentioning
confidence: 99%
“…No studies have directly compared the type of anthracycline used for induction and consolidation, although a recent matched‐pair analysis comparing idarubicin and daurorubicin showed no significant difference in antileukaemic effect (Sanz et al , ).…”
Section: Open Issues With Atra and Chemotherapymentioning
confidence: 99%
“…Although no significant differences in the proportion of deaths due to haemorrhage, infection and DS was observed, DS‐associated mortality among those patients developing moderate or severe DS was significantly higher in the IC‐APL study compared with PETHEMA/HOVON study (12% vs. 3%, respectively; P = 0·01) (Sanz et al , ). Another difference between the studies was seen in non‐relapse mortality during consolidation, which was higher in IC‐APL (4·8% vs. 1·2%; P = 0·04) (Sanz et al , ). The most likely explanation for these discrepancies is differences in supportive care, management of DS and suboptimal prevention and treatment of infections during consolidation therapy in the IC‐APL cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The IC‐APL trial had an identical treatment to that the LPA2005 trial, except for the replacement of idarubicin by daunorubicin, and this similar design offered a unique opportunity to compare the outcomes of a study conducted in developing countries (IC‐APL) to those in developed countries (PETHEMA/HOVON). A matched‐pair analysis was performed to minimize the effects of non‐treatment‐related variables on outcomes (Sanz et al , ), which showed that daunorubicin and idarubicin have similar anti‐leukaemic efficacy in terms of primary resistance and molecular persistence, as well as molecular and haematological relapse rates. A cost/effectiveness analysis was not performed, but we consider that the proposed policy was highly effective and applicable to other developing countries, based on the fact that the standard treatment still is considered to be ATRA and anthracycline and that daunorubicin has the lowest cost among the anthracyclines with similar anti‐leukaemic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Karim et al 20 in a study with 26 patients, found a 11.5% relapse rate of both molecular and of the central nervous system (CNS). In the matched-pair analyses of the PETHEMA LPA-2005 and IC-APL-2006 studies, 21 relapse rates were 7.4% and 5%, respectively. No CNS relapse was detected in this series.…”
Section: Discussionmentioning
confidence: 99%